Pengaruh Jenis Sekrap Aluminium Yang dilebur terhadap sifat fisis dan mekanis Produk rumah Pompa Hidrolik - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
The objective of the research is to know the effect of scraps types that were molten to physical and mechanical properties of aluminium casting .The toughness, hardness, porosity and microstructure properties were studied.The type of scrap sused in this research were aluminum scrap from pipe, piston and car wheel.The result of the research show that, the combination of 15% car wheel scrap and 85% aluminum pipe scrap is the best scrap combination to produce exeternal gear pump casing.